(untitled) (Research, Society and Development, 2022)
This study aimed to evaluate the sexual behavior and fertility of ewes and ewe lambs after the application of an estrous induction/synchronization protocol using GnRH. The females were randomly distributed in two experimental groups: group 1 (G1) was composed of pluriparous ewes aged 2 to 3 years, and group 2 (G2) was composed of ewe lambs, aged 7 to 8 months. All females were subjected to the Ovsynch protocol, which consisted of GnRH administration on day 0 (D0), d-cloprostenol seven days later (D7), and a second dose of GnRH (D9) was administered 48 hours later. Estrus observations were initiated immediately after PGF2α application, and were performed three times daily, lasting 4 days. The animals of G2 did not manifest signs of estrus. Of the total treated females in G1, 85.7% showed signs of estrus. The pregnancy rate obtained in G1 animals was 83.3% (5/6), which was confirmed by a positive pregnancy diagnosis at 40 days post-coverage. In conclusion, the results showed that the hormonal treatment Ovsynch was efficient in inducing/synchronizing estrus, as well as producing high pregnancy rate in pluriparous ewes. However, the same protocol was not efficient in young animals (ewe lambs).